Hakikat Manusia (Anak Didik) Sebagai Makhluk Pedagogik - Sulkifli; Yuspiani (Program Studi Pendidikan Teknologi Informasi Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2025)
This research examines the nature of humans as pedagogical beings with a focus on students in the perspective of Islamic education. Humans are created with fitrah and basic potential that allows them to learn and develop. This research uses a literature review method with a philosophical-normative approach to analyze the concept of fitrah as basic potential, as well as the role of hearing, sight, and heart as the main learning instruments. The results show that humans have an inherent capacity to receive education through three main instruments bestowed by Allah swt. Human fitrah as pedagogical beings becomes the fundamental foundation in developing holistic education systems. The implications of this research contribute to understanding the basic concepts of Islamic education and developing learning methodologies that are in accordance with human nature.